2017
DOI: 10.4172/2329-9096.1000418
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of Virtual Reality Training on Balance and Gait Recovery Early after Stroke: A Pilot Study

Abstract: Objective: To investigate the feasibility and effectiveness of virtual reality training for improving balance and/or gait during inpatient rehabilitation of patients within 12 weeks after stroke. Methods:Sixteen patients within 12 weeks after stroke and dependent gait as categorised with a Functional Ambulation Category score of 2 or 3 were included in this longitudinal pilot study. Participants received eight 30-min sessions of virtual reality training during four weeks as part of the regular inpatient rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…On the other hand, informal caregivers often lack knowledge and support and they need more education on how they can provide support with exercise and physical activity [22,23]. Many studies have revealed a need for practical support for stroke survivors and their informal caregivers to help them engage in home-based exercise [10], and recent studies have suggested support could be provided by technical applications [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, informal caregivers often lack knowledge and support and they need more education on how they can provide support with exercise and physical activity [22,23]. Many studies have revealed a need for practical support for stroke survivors and their informal caregivers to help them engage in home-based exercise [10], and recent studies have suggested support could be provided by technical applications [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…107,109 Likewise, though not evaluated in our review, VR training was also beneficial for balance-related outcomes in stroke survivors. Many of the included studies in our review reported an enhancement in static and dynamic balance with VR as demonstrated by an increased Berg balance score, 64,83,88 timed up and go test, 70,84 and functional reach test. 64,67 Here, the literature suggests that the rehabilitation by VR was superior compared with conventional therapy because of its ability to allow a multisensory learning environment and its ability to motivate and simulate new motor and sensory abilities responsible for maintaining balance.…”
Section: Discussionmentioning
confidence: 95%
“…Of the 32 included studies, 20 were RCTs 58-77 and 12 were CCTs. [78][79][80][81][82][83][84][85][86][87][88][89] Interventions Of all the included studies, 18 analyzed the influence of VR training on gait parameters, 39,60,[63][64][65][66]69,[71][72][73]75,77,78,[81][82][83][84][85]87 eight used VR in adjunct with treadmill, 61,62,64,67,68,70,77,89 and six used VR with robot-assisted training. 58,59,74,79,80,86 In terms of control interventions for 20 RCTs, the influence of VR training was compared in nine studies with conventional rehabilitation, 60,63,65,67,…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The GRAIL consists of a dual-belt treadmill with force platform, a motion-capture system (Vicon Motion Systems, Oxford, UK) and a 180° semi-cylindrical screen for the projection of environments with optic flow (Fig. 3) [28]. During the training sessions participants wear a safety harness that is attached to an overhead suspension system.…”
Section: Methodsmentioning
confidence: 99%